Synthesis of aryl-thioglycopeptides through chemoselective Pd-mediated conjugation. Issue 46 (26th September 2018) - Montoir, David; Amoura, Mehdi; Ababsa, Zine El Abidine; Vishwanatha, T. M.; Yen-Pon, Expédite; Robert, Vincent; Beltramo, Massimiliano; Piller, Véronique; Alami, Mouad; Aucagne, Vincent; Messaoudi, Samir
Abstract : A highly chemoselective thioglycoconjugation method of iodoaryl aminoacids, small peptides and complex unprotected polypeptides is reported. Abstract : We describe herein a Pd-catalyzed methodology for the thioglycoconjugation of iodoaryl peptides and aminoacids. This operationally simple process occurs under semi-aqueous conditions and displays wide substrate scope. The strategy has been successfully applied to both the thioglycosylation of unprotected peptides and the generation of thioglyco-aminoacid building blocks, including those suitable for solid phase peptide synthesis. To demonstrate the broad potential of this technique for late stage functionalization, we successfully incorporated challenging unprotected β- S -GlcNAc- and α- S -GalNAc-derivatives into very long unprotected peptides. This study opens the way to new applications in chemical biology, considering the well-recognized advantages of S -glycosides over O -glycosides in terms of resistance towards both enzymatic and chemical degradation.